تحديات تنفيذ أحكام التحكيم الأجنبية في النزاعات الناشئة عن عقود التمويل الإسلامي : دراسة تحليلية في دول مجلس التعاون الخليجي وماليزيا - شحري، محمد بن أحمد جناشال (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2017)
This study deals with “the challenges in enforcement of foreign arbitral awards on disputes arising out of Islamic Finance agreements (the case of GCC and Malaysia)”. This dissertation explains the difficulties, which come across in enforcement of foreign arbitral awards, especially in the disputes arising out of Islamic Finance agreements where no unified binding international law exists that regulates the relation among the Islamic Finance contracting parties in conformity with Sharia'h. Although these awards are issued in cases of contracts coming from the rules of Sharia'h, these awards are facing difficulties and challenges in enforcement, because the enforcement is subject to laws, regulations and procedures of the courts of these countries. The researcher has adopted inductive, analytical and comparative approach in order to identify the rules and regulations for enforcement of foreign arbitral awards in the countries of the subject study which are Malaysia and GCC, and in international and regional agreements to know the enforcement challenges. The study has dealt with the concept of arbitration and Islamic Finance, arbitration procedures in Islamic Finance contracts disputes, and previous arbitration cases on Islamic Finance contracts. It also reviews the challenges in enforcement of foreign arbitral awards under national laws of the country the award is issued, and the country that will enforce the award, and also the challenges in enforcement of the final arbitral awards in the international agreements (Agreement on Enforcement of Judgments, Representations and Judicial Notifications in the Arab GCC States, 1997 and New York Convention on Recognition and Enforcement of Foreign Arbitral Awards, 1958). The study lead to a number of conclusions, most importantly: that arbitration is a preferred mode of dispute resolution for Islamic Finance firms because the parties can choose Islamic Law as substantive law to be applicable in disputes arising out of Islamic Finance agreements. Challenges in enforcement still exist despite the availability of agreements where these agreements even represent public policy concept and the conditions found in the national laws. The study suggests there should be special legislations that provides for mechanism of enforcement of foreign arbitral awards related to Islamic Finance agreements.